Scaling the primate lateral geniculate nucleus: Niche and neurodevelopment in the regulation of magnocellular and parvocellular cell number and nucleus volume. Issue 8 (1st June 2014) - Finlay, Barbara L.; Charvet, Christine J.; Bastille, Isle; Cheung, Desmond T.; Muniz, José Augusto P.C.; de Lima Silveira, Luiz Carlos
ABSTRACT New stereological assessments of lateral geniculate nucleus (LGN) neuron numbers and volumes in five New World primates (Cebus apella, Saguinus midas niger, Alouatta caraya, Aotus azarae, and Callicebus moloch) and compiled LGN volumes for an additional 26 mammals were analyzed for a better understanding of visual system evolution. Both the magnocellular (M)‐ and the parvocellular (P)‐cell populations scale allometrically with brain volume in primates, P cells with a significantly higher slope such that, for every increase in M neuron number, P neuron numbers more than double (ln scale; y = 0.89x + 2.42R2 = 0.664). In diurnal primates, the ratio of P to M cells was slightly but significantly higher than in nocturnal primates. For all mammals, including primates, LGN volume was unrelated to nocturnal or diurnal niche but showed marked differences in slope and intercept depending on taxonomic group. The allometric scaling of M and P cells can be related to the order of neurogenesis, with late‐generated P cells increasing with positive allometry compared with the earlier‐generated M cells. This developmental regularity links relative foveal representation to relative isocortex enlargement, which is also generated late. The small increase in the P/M cell ratio in diurnal primates may result from increased developmental neuron loss in the M‐cell population as it competes for limited termination zones in primary visual cortex. J. Comp. Neurol. 522:1839–1857, 2014. © 2013 Wiley Periodicals, Inc.